Pengaruh Rasio Keuangan Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Sektor Pertambangan Terdaftar di Bursa Efek Indonesia tahun 2019-2023) - Septianingsi Septianingsi; Yudi Yudi; Lutfi Lutfi (Journal of Innovative and Creativity, 2025)
Firm value reflects investors’ perceptions of a company’s performance and long term prospects. Various internal factors, such as financial ratios, are often used as key indicators to assess such performance. This study aims to analyze the effect of financial ratios consisting of profitability, liquidity, and leverage on firm value, as well as to examine the role of firm size as a moderating variable. This research employs a quantitative approach using Structural Equation Modeling (SEM) Partial Least Squares (PLS) analysis with WarpPLS 8.0 software. Secondary data were obtained from the financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with a population of 112 companies. The sampling technique used was purposive sampling, resulting in 34 companies that met the criteria. The findings indicate that profitability and leverage significantly affect firm value, while liquidity has no significant effect. Moreover, firm size is unable to moderate the relationship between profitability, liquidity, and leverage on firm Keywords: Profitability, Liquidity, Leverage, Firm Size, Firm Value. value.